ON SOME EFFECTS IN THE STRUCTURE OF WHITE DWARFS - B.A. Zhami; K.Boshkayev; H. Quevedo; Zh.A. Kalymova (Academic Scientific Journal of Computer Science, 2019)
We review the effects of general relativity, finite temperatures, nuclear composition and rotation which make a substantial contributionto the structure of white dwarfs.First, the mass-radius, mass-central density relations and mass, density profiles of a white dwarf with total mass1.415 M⨀ are constructed both in Newtonian gravity and general relativity, which clearly show that the general relativistic effects are significant for massive white dwarfs close to the Chandrasekhar mass limit, consequently, in strong gravitational fields.Second, hot white dwarfs are studied in the framework of general relativity. Basic parameters of white dwarfs such as the central density, pressure, mass, radius and etc. are calculated. It is shown that the effects of finite temperatures play a key role in low mass white dwarfs.Third, cold white dwarfs are investigated within general relativity employing the Salpeter equation of state. Finally, we investigate the equilibrium configurations of uniformly rotating white dwarfs, using Chandrasekhar and Salpeter equations of state in Newtonian gravity and plot mass-radius, mass-central density relations. It is demonstrated that the effects of rotation are essential in the structure of white dwarfs in allmass range.